Utilization of palm oil boiler ash (POBA) as geopolymer material for industrialized building system (IBS) application / Zarina Binti Yahya. - Zarina Yahya (School of Materials Engineering, Universiti Malaysia Perlis, 2015)
The aim of this study is to develop POBA geopolymer paste and the production of geopolymer brick and IBS bring using geopolymerization process.